Life without Language. (3rd July 2017) - Dong, Xi; King, Dylan Levi
Abstract : Dong Xi's first major novella, published first in Harvest in 1996, winner of the Lu Xun National Excellent Novella Award, and adapted into a CCTV-8 television series in 2009 (as Sky Lovers) takes the form of a modern parable, telling the story of Wang Jiakuan, who is deaf; Wang Laobing, who is blinded in an accident; and Cai Yuzhen, who cannot speak. Wang Jiakuan and Cai Yuzhen meet and fall in love and live with Wang Laobing. The trio work together to get by in a cruel world, eventually bring a child into the world, and then finally withdraw from society.